Stable Isotope Ecology of Invasive Lionfish (Pterois volitans and P. miles) in Bermuda - Eddy, Corey; Pitt, Joanna M.; Larkum, Jennifer; Altabet, Mark A.; Bernal, Diego (Frontiers in Marine Science, 2020)
Over the past three decades, lionfish (Pterois volitans and P. miles) from the Indo-Pacific have invaded the northwest Atlantic Ocean, Caribbean Sea and the Gulf of Mexico. As generalist predators with a broad diet, they could pose a major threat to economically and ecologically important species and, therefore, the overall health of coral reef ecosystems and the communities that rely on them. In Bermuda, the lionfish invasion appears to be progressing at a slower rate than elsewhere in the invaded range, providing an opportunity to study their ecological impact at an early stage. This study used stable isotope analysis of lionfish, their major prey, and their competitors to investigate the feeding ecology of lionfish in Bermuda and provide a more complete evaluation of their potential impacts on community structure and trophic interactions. Results suggest that lionfish in Bermuda primarily derive resources from the plankton-based food web, with only a small contribution from food chains supported by macroalgae. Further, it appears that lionfish resource use overlaps substantially with other similarly-sized sympatric mesopredators, in particular the coney grouper (Cephalopholis fulva), a species commonly targeted by local commercial fisheries. This visualization of Bermuda’s demersal ecosystem in two-dimensional isotope space, the first of its kind, will help track the ecological impact of lionfish over time, predict potential changes in community structure, and better inform developing control strategies for this invasive species.